Molecular Epidemiology of Staphylococcus aureus Bacteremia: Association of Molecular Factors With the Source of Infection - Pérez-Montarelo, Dafne; Viedma, Esther; Larrosa, Nieves; Gómez-González, Carmen; Ruiz de Gopegui, Enrique; Muñoz-Gallego, Irene; San Juan, Rafael; Fernández-Hidalgo, Nuria; Almirante, Benito; Chaves, Fernando (Frontiers in Microbiology, 2018)
Staphylococcus aureus bacteremia (SAB) is associated with high morbidity and mortality, which varies depending on the source of infection. Nevertheless, the global molecular epidemiology of SAB and its possible association with specific virulence factors remains unclear. Using DNA microarrays, a total of 833 S. aureus strains (785 SAB and 48 colonizing strains) collected in Spain over a period of 15 years (2002–2017) were characterized to determine clonal complex (CC), agr type and repertoire of resistance and virulence genes in order to provide an epidemiological overview of CCs causing bloodstream infection, and to analyze possible associations between virulence genes and the most common sources of bacteremia. The results were also analyzed by acquisition (healthcare-associated [HA] and community-acquired [CA]), methicillin-resistant (MRSA) and methicillin-susceptible (MSSA) strains, and patient age (adults vs. children). Our results revealed high clonal diversity among SAB strains with up to 28 different CCs. The most prevalent CCs were CC5 (30.8%), CC30 (20.3%), CC45 (8.3%), CC8 (8.4%), CC15 (7.5%), and CC22 (5.9%), which together accounted for 80% of all cases. A higher proportion of CC5 was found among HA strains than CA strains (35.6 vs. 20.2%, p < 0.001). CC5 was associated with methicillin resistance (14.7 vs. 79.4%, p < 0.001), whereas CC30, CC45, and CC15 were correlated with MSSA strains (p < 0.001). Pathogen-related molecular markers significantly associated with a specific source of bacteremia included the presence of sea, undisrupted hlb and isaB genes with catheter-related bacteremia; sed, splE, and fib genes with endocarditis; undisrupted hlb with skin and soft tissue infections; and finally, CC5, msrA resistance gene and hla gene with osteoarticular source. Our study suggests an association between S. aureus genotype and place of acquisition, methicillin resistance and sources of bloodstream infection, and provides a valuable starting point for further research insights into intrinsic pathogenic mechanisms involved in the development of SAB.